2021
DOI: 10.1177/10634266211060079
|View full text |Cite
|
Sign up to set email alerts
|

Too Anxious to Talk: Social Anxiety, Academic Communication, and Students’ Experiences in Higher Education

Abstract: Social anxiety is related to a host of negative student outcomes in the educational context, including physical symptoms of anxiety, reduced cognitive functioning, and poor academic performance. Despite the prevalence of social anxiety, little is known about mechanisms that may underlie associations between social anxiety and outcomes in the context of higher education. Therefore, the goal of this study was to evaluate a conceptual model linking social anxiety, communication with peers and instructors, student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 64 publications
1
23
0
2
Order By: Relevance
“…This result further confirmed the adverse influence of social phobia on academic performance ( Baptista et al, 2012 ; Leigh et al, 2021 ; Vilaplana-Pérez et al, 2021 ; Archbell and Coplan, 2022 ) and on L2 acquisition and learning ( King, 2013a , b ). Meanwhile, the current research provided much empirical evidence and specifically elucidated how and to what extent social phobia could affect L2 WTC.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This result further confirmed the adverse influence of social phobia on academic performance ( Baptista et al, 2012 ; Leigh et al, 2021 ; Vilaplana-Pérez et al, 2021 ; Archbell and Coplan, 2022 ) and on L2 acquisition and learning ( King, 2013a , b ). Meanwhile, the current research provided much empirical evidence and specifically elucidated how and to what extent social phobia could affect L2 WTC.…”
Section: Discussionsupporting
confidence: 73%
“…Researchers also detected that the adverse impact of social phobia would remain enduring across the lifespan. Archbell and Coplan (2022) also discovered that social phobia was negatively correlated with the academic communication with instructors.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Our finding of association between perceived unavailability of support to schoolwork when needed, and high social anxiety was expected and might relate to findings on socially anxious adolescents’ multiple problems in educational functioning and in communicating their needs for support to adults, such as teachers [ 60 ]. Expressing need for support might be even more difficult and complicated during COVID-19 pandemic, and yet continued support may be especially important for these adolescents.…”
Section: Discussionmentioning
confidence: 66%
“…The positive effect of student-faculty interaction on students' academic well-being was more pronounced among females, and female students were also more likely to engage in one-on-one academic interaction with teachers (Kim, 2019). Archbell and Coplan (2021) indicated that women exhibited more sensitivity in student-faculty interaction and higher level of social anxiety compared to men. These studies reflect differences in the functions performed by student-faculty interaction that may result from gender differences, with male students being more motivated to engage in social studentfaculty interaction, while female students tend to be academicoriented in their interaction.…”
Section: Gender Differences In the Mediating Role Of Student-faculty ...mentioning
confidence: 96%